2011
DOI: 10.1371/journal.pone.0020223
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF Mass Spectrometry Is a Fast and Reliable Platform for Identification and Ecological Studies of Species from Family Rhizobiaceae

Abstract: Family Rhizobiaceae includes fast growing bacteria currently arranged into three genera, Rhizobium, Ensifer and Shinella, that contain pathogenic, symbiotic and saprophytic species. The identification of these species is not possible on the basis of physiological or biochemical traits and should be based on sequencing of several genes. Therefore alternative methods are necessary for rapid and reliable identification of members from family Rhizobiaceae. In this work we evaluated the suitability of Matrix-Assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 82 publications
2
65
0
8
Order By: Relevance
“…These advantages, along with the proven accuracy of MALDI-TOF MS-based identification of bacteria, have revolutionized the routine identification of microorganisms to species and subspecies level in clinical diagnostic and food microbiological laboratories (Croxatto et al 2012;Mazzeo et al 2006). MALDI-TOF MS has also been shown to be an excellent tool for identification of diverse rhizobial species of Bradyrhizobium, Ensifer, Shinella, and Rhizobium applicable to large populations of isolates in ecological and taxonomic studies (Ferreira et al 2011;Sánchez-Juanes et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These advantages, along with the proven accuracy of MALDI-TOF MS-based identification of bacteria, have revolutionized the routine identification of microorganisms to species and subspecies level in clinical diagnostic and food microbiological laboratories (Croxatto et al 2012;Mazzeo et al 2006). MALDI-TOF MS has also been shown to be an excellent tool for identification of diverse rhizobial species of Bradyrhizobium, Ensifer, Shinella, and Rhizobium applicable to large populations of isolates in ecological and taxonomic studies (Ferreira et al 2011;Sánchez-Juanes et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MALDI-TOF MS analysis using the rhizobia-specific database grouped RNB strains into genera and species congruent with the phylogenies obtained using marker gene sequences (16S rRNA, MLSA) and consistent with classifications previously obtained for cluster analysis of MALDI-TOF spectra of Ensifer and Rhizobium spp. (Ferreira et al 2011). The database also provided an accurate and highly resolved analysis of strain diversity at the species and often subspecies level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By generating unique whole-cell protein-based fingerprints for each colony, the Biotyper permits highly reproducible identification of bacterial colonies to the genus or species level. Because of its reproducibility, ease of use, and cost effectiveness, the Biotyper is used extensively in clinical and public health microbiological laboratories (53) and is finding increased use in ecological studies (54)(55)(56). To standardize growth prior to analysis, individual colonies were tooth-picked onto a one-third TSA plate and grown overnight.…”
Section: Methodsmentioning
confidence: 99%
“…La rapidez y relativa sencillez del uso de la espectrometría de masas ya ha demostrado su utilidad en comparación con otros sistemas diagnósticos en el laboratorio de microbiología (18)(19)(20)(21). El diagnós-tico del agente etiológico productor de la bacteriemia requiere el cultivo previo del microorganismo en medio sólido desde los frascos de hemocultivo positivo, lo que supone un retraso de al menos 8-24 horas.…”
Section: Discussionunclassified